COMPARISON BETWEEN EFFICACY OF MDI+SPACER AND NEBULISER IN THE MANAGEMENT OF ACUTE ASTHMA IN CHILDREN - Fayaz, Mohammad; Sultan, Ambreen; Rai, Manzoor Elahi (Journal of Ayub Medical College Abbottabad, 2009)
Background: Due to changing evidence on efficacy of MDI+spacer as compared to nebuliser, two types of managements were going on in our Day unit, depending on the presence of different medical professionals. We wanted to find out the evidence of the best practice from within our unit, and then to formulate guidelines based on it for the management of paediatric acute asthma. Methods: We isolated 54 cases of children suffering from acute asthma attack from admissions during Oct 2004-March 2005 within the age range of 3-14 yrs. We categorised them into four classes of mild, moderate, severe and life threatening acute attack depending on its severity and then separated them in two groups. Group I received salbutamol Via MDI+spacer and Group II received salbutamol via nebuliser. Our outcome measure was time to clinical improvement and duration of hospital stay. Results: We didn't find any major difference between the two groups, moreover MDI+spacer was better than nebuliser for the treatment of severe acute asthma attack in children. Conclusion: Our study supported and confirmed the evidence that MDI+spacer is least as effective as nebuliser in the management of acute asthma in children. Keywords: MDI+spacer, Nebuliser, Juvenile Asthma, Salbutamol, Wheeze